Contact calling in context: intra- and intergroup variation in vocalization rates depend on a call’s function - Chaverri Echandi, Gloriana (2020)
To maintain group cohesion while coordinating group movements, individuals might use signals to advertise the location of a route, their intention to initiate movements, or their position at a given time. In highly mobile animals, the latter is often accomplished through contact calls that are emitted at different rates by group members. Here, we describe and quantify intra- and intergroup variation in contact calling rates in Spix’s disc-winged bats (Thyroptera tricolor), a species that employs distinct inquiry and response calls to coordinate group movements during flight and while announcing roost locations. We evaluate the extent to which groups are composed of individuals with similar calling rates and estimate variation among and within groups. Our results show large variation in response calling rates among and within groups, both in terms of calling rates and the probability of being vocal or not; for example, a large portion (35%) of bats sampled did not produce these signals. For inquiry calls, we found that variation in calling rates was greater within than among groups, and in contrast to response calls, only a few individuals (3%) did not produce inquiry calls. Overall, we found support for the existence of intra- and intergroup differences in the context of contact calling in disc-winged bats, and our results suggest that different mechanisms may promote the evolution and maintenance of varying calling rates for the two types of calls studied.